Juego coreográfico: "En el Punto", memoria de investigación a partir de la elaboración de la panela en Chaparral Tolima. (2024)
This thesis is an investigation-creation of a choreography play about the cane sugar production from traditional rhythms of Tolima as guabina and caña/bambuco fiestero, based on the investigation did on municipality of Chaparral, specific on vereda1 La Cortés, on 2024.